Queueing systems with random volume customers and a sectorized unlimited memory buffer - Tikhonenko, Oleg; Ziółkowski, Marcin; Kempa, Wojciech M. (Zielona Góra: Uniwersytet Zielonogórski)
In the present paper, we concentrate on basic concepts connected with the theory of queueing systems with random volume customers and a sectorized unlimited memory buffer. In such systems, the arriving customers are additionally characterized by a non-negative random volume vector. The vector`s indications can be understood as the sizes of portions of information of a different type that are located in the sectors of memory space of the system during customers` sojourn in it.
Keywords: queueing systems with random volume customers; sectorized memory buffer; total volume vector; Laplace and Laplace?Stieltjes transforms; multi-variate L`Hospital rule